PENULISAN DAN PUBLIKASI ARTIKEL ILMIAH UNTUK MENINGKATKAN KOMPETENSI GURU - Rosa, Novrita Mulya; Suryadi, Ahmad (UNIVERSITAS SERAMBI MEKKAH, 2024)
The skill of writing scientific articles is a reflection of the quality of a professional teacher. This community service activity was motivated by the lack of understanding and ability of teachers at Al-Hikmah Islamic Middle School in preparing scientific articles. Many teachers are still reluctant to publish research results on the grounds that they do not understand the guidelines for preparing scientific articles. This is what underlies the need to carry out this service activity with the aim of assisting teachers in compiling scientific articles so that later teachers can publish articles that have been written in journals or proceedings. Service activities were carried out at Al-Hikmah Islamic Middle School, South Jakarta. In this Community Service activity, the team provided counseling on writing and publishing scientific articles to improve teacher competency. The activity stages consist of preparation, implementation and evaluation. The preparation stage begins with a survey of partners to find out the problems faced by partners. The community service implementation stage is carried out online using the Zoom application to deliver outreach material. At the end of the stage, there is an evaluation of the activities carried out, it is hoped that there will be an increase in teacher knowledge and skills in writing and publishing scientific articles. The planned output target for this activity is to increase teachers' insight and skills in writing and publishing scientific articles. The output of community service will be published in the form of scientific articles in journals.